Human footprint [videorecording (DVD)] - Dappen, Nate; Losin, Neil; Campbell-Staton, Shane (PBS, 2023)
Earth has never experienced anything like us: a single species dominating and transforming the planet. Biologist Shane Campbell-Staton travels the world to explore our global impact. Because while we may tell ourselves what it means to be human, the clearest vision of who we are emerges from what we do.